Biological control potential of the spotted stem borer Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) with the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae - Mekonnen, Tadele Tefera; Tadele Tefera (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Agric))--University of Stellenbosch, 2004.